Capitalisms and Gay Identities - Valocchi, Stephen M., 1956- (New York : Routledge, 2019)
In this important text, Stephen Valocchi brings capitalism back into the study of the gay and lesbian movement. He argues that to understand the collective identity, structure, strategies and goals of the movement, we need to understand the role that capitalism and the state have played. While capitalism and the state have figured centrally in earlier analyses of social movements, these important institutions and their social processes are no longer central concerns of the theory and research of social movements in the United States. Capitalisms and Gay Identities examines how the class-based inequalities and changing class structures of capitalism interact with and indeed help shape the dynamics of other types of inequalities, such as gender, sexuality, race and ethnicity. These inequalities and structures, in turn, shape the specific grievances of, and affect the nature of, stigma levied against individuals with sexual and gender nonconformity. Valocchi shows that capitalism is a dynamic system, and as it changes, the nature of the movement and the collective identity created by the movement also changes. A vital text for undergraduate and postgraduate students of sociology, social movements, LGBTQ politics and American studies, Capitalisms and Gay Identities challenges our understanding of many aspects of the gay and lesbian movement when viewed through the lens of capitalism, particularly its ability to advance the cause of sexual freedom and gender justice.
Cover; Title Page; Copyright Page; Table of Contents; List of Photographs; 1: Introduction; 2: Capitalism and Studying LGBT Social Movements and Identities since World War II; 3: The Homophile Movement and the Making of a Psychiatric Collective Identity; 4: The Gay Rights Movement, and the Making of a Minority Identity; 5: Contested Minority Identity and the Religious Right; 6: The Movement Inc., and the Rise of a Domesticated and Consumerist Gay Identity; 7: Rethinking Progress and Identity: Political Economy and Sexual and Gender Liberation; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Gay Studies; POLITICAL SCIENCE / General; Gay liberation movement; Capitalism